Whole transcriptomic analysis of mesenchymal stem cells cultured in Nichoid micro-scaffolds - Testa, Carolina; Oliveto, Stefania; Jacchetti, Emanuela; Donnaloja, Francesca; Martinelli, Chiara; Pinoli, Pietro; Osellame, Roberto; Cerullo, Giulio; Ceri, Stefano; Biffo, Stefano; Raimondi, Manuela T. (Frontiers in Bioengineering and Biotechnology, 2023)
Mesenchymal stem cells (MSCs) are known to be ideal candidates for clinical applications where not only regenerative potential but also immunomodulation ability are fundamental. In the last years, increasing efforts have been put in the design and fabrication of 3D synthetic niches, conceived to emulate the native tissue microenvironment and aiming at efficiently control MSCs phenotype in vitro. In this panorama, our group patented an engineered microstructured scaffold, called Nichoid. It is fabricated by two-photon polymerization, a technique enabling the creation of 3D structures with control of the scaffold geometry at the cell level and with a spatial resolution beyond the diffraction limit, down to 100 nm. The Nichoid capacity to maintain higher levels of stemness as compared to 2D substrates, without the need of adding any exogenous soluble factor, has already been demonstrated in MSCs, neural precursors and murine embryonic stem cells. In this work, we evaluated how three-dimensionality can influence the whole gene expression profile in rat MSCs. Our results show that, at only 4 days from cell seeding, gene activation is affected in a significant way, since 603 genes appear to be differentially expressed (364 up-regulated and 239 down-regulated) between cells cultured in 3D Nichoids and in 2D controls. The functional enrichment analysis shows that differentially expressed genes are mainly enriched in pathways related to actin cytoskeleton, extracellular matrix (ECM) and, in particular, cell adhesion molecules (CAMs), confirming the important role of cell morphology and adhesions in determining MSCs phenotype. In conclusion, our results suggest that the Nichoid, thanks to its exclusive architecture and 3D cell adhesion properties, is not only a useful tool for governing cell stemness but could also be a mean for controlling immune-related MSCs features specifically involved in cell migration.